Looking beyond the lesbian: The intersectionality of death on Netflix's Orange is the New Black. Issue 4 (2nd October 2019) - Ruderman-Looff, Ashley
Abstract: In 2016, GLAAD's "Where We Are On TV" report noted a significant rise in lesbian death. This article addresses this perpetual trend as it manifests within Netflix's Orange is the New Black by considering the deaths of Tricia Miller and Poussey Washington. I use a narrative form of intersectional analysis to argue that lesbian death initiates a powerful critique of the criminal legal system and the prison industrial complex. Specifically, lesbian death points to the way multiple modes of marginalization intersect with homophobia to buttress a system designed to administer social and premature death. My analysis of Tricia's death demonstrates how the school-to-prison pipeline prepares children to take responsibility for their behaviors, but neglects to address how their futures in the justice system are systematically produced and beyond their control. This message corresponds to Tricia's flashbacks and her suicide, which demonstrate how, under neoliberalism, Tricia's failure to "pull herself up" leads to her incarceration. In turning to Poussey, I argue that reading her death as an accident not only dismisses the "one bad apple" myth typically used to account for police brutality, it demonstrates how "accidental death" is systematically and deliberately produced within the prison industrial complex. I analyze flashbacks of both Poussey and her killer, Baxter Bayley, to draw attention to the fact that they have committed the same crimes. I demonstrate how power and criminalization are assigned on the basis of gender, race, sexuality, and class.